Biological effects of TNF in turbot (Scophthalmus maximus) and characterization of TNF-α receptors - Dios, S.; Romero Jódar, Alejandro; Montes, Ariana; Figueras Huerta, Antonio; Novoa, Beatriz (2010)
1st EOFFI Symposium, First Symposium of the European Organisation of Fish Immunology, Viterbo (Italia), 23-25 May 2010 No